Conceptual framework on noise ranking classification in eatery places for human psycho-acoustics preferences towards acoustic comfort - Che Din, Nazli; Mistar, Noor Aini; Sulaiman, Raha; Abdullah, Zunaibi; Yahya, Musli Nizam; Haron, Zaiton (2022)
One of the important dining interests for focusing on smelling and tasting during dining in eatery places is having concentration or attention perceived of what we eat or drink. The dining satisfaction influenced positive behavior of return intent and recommending the eatery places to others. Higher noise level may distract the concentration for having a fine dining experience and could interrupt the ability of smelling and tasting senses. Settings in the noisy atmosphere of eatery places such as located near to a busy road, open kitchen, table layout and inappropriate decoration as well as the patrons’ conversation behavior may affect speech intelligibility. Ultimately, the long period exposure towards high decibel sound and noise affecting not only the health and wellbeing but also the social interactions and communications. It is also having a direct significant impact to human preferences on acoustic comfort during their dining. However, there is no specific classification or rating system established in Malaysia to assist the information on acoustic environment obtained in the eatery place. The aim of this paper is to identify the framework of eatery places classification in Malaysia within the context of the acoustic comfort and its performance. The main concern is to elucidate clearly different categorization of eatery places which might have significant on human psychoacoustics. Based on ongoing research, this paper will discuss on the critical literature reviews to develop a conceptual framework in classifying eatery places typologies and diners’ acoustical preferences.